2020
DOI: 10.3390/foods9081120
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Potentially Bioactive Compounds in Italian Extra Virgin Olive Oils from Various Sources by Using LC-MS and Multivariate Data Analysis

Abstract: High quality extra virgin olive oils represent an optimal source of nutraceuticals. The European Union (EU) is the world’s leading olive oil producer, with the Mediterranean region as the main contributor. This makes the EU the greatest exporter and consumer of olive oil in the world. However, small olive oil producers also contribute to olive oil production. Beneficial effects on human health of extra virgin olive oil are well known, and these can be correlated to the presence of vitamin E and phenols. Togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 37 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…The findings of this study are in agreement with previous ones with the highest secoiridoid concentration and the lowest flavonoid and phenolic alcohol concentrations (except Taounate province) [ 35 ]. The values attained for tyrosol in VOOs coming from Chefchaouen (300.57 mg kg −1 ) and Beni Mellal (186.17 mg kg −1 ) are much higher with respect to the mean value for commercial extra virgin olive oils (EVOOs) belonging to the Italian and European markets (56 mg kg −1 ) [ 36 ] This can be justified by the hydrolysis of oleuropein and oleacine [ 13 ]. These values are not in agreement with a previous work by Bajoub et al, who reported that a mean concentration of tyrosol in VOOs of Picholine marocaine from Chefchaouen, Taounate and Taza provinces ranged from 4.43 mg kg −1 to 7.46 mg kg −1 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study are in agreement with previous ones with the highest secoiridoid concentration and the lowest flavonoid and phenolic alcohol concentrations (except Taounate province) [ 35 ]. The values attained for tyrosol in VOOs coming from Chefchaouen (300.57 mg kg −1 ) and Beni Mellal (186.17 mg kg −1 ) are much higher with respect to the mean value for commercial extra virgin olive oils (EVOOs) belonging to the Italian and European markets (56 mg kg −1 ) [ 36 ] This can be justified by the hydrolysis of oleuropein and oleacine [ 13 ]. These values are not in agreement with a previous work by Bajoub et al, who reported that a mean concentration of tyrosol in VOOs of Picholine marocaine from Chefchaouen, Taounate and Taza provinces ranged from 4.43 mg kg −1 to 7.46 mg kg −1 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of phenolic compounds from VOO was determined following a protocol described previously [ 36 , 41 , 42 ]. Briefly, 1 g of VOO was dissolved in 1 mL of n -hexane, and then hexane phase was discarded.…”
Section: Methodsmentioning
confidence: 99%
“…Extra virgin olive oil (EVOO) is a high-value product due to its excellent nutritional properties and organoleptic characteristics, which are appreciated for their positive effect on human health. It is an important part of the Mediterranean diet due to the beneficial effects related to fat composition [ 1 , 2 , 3 , 4 ], which includes monounsaturated, polyunsaturated, and saturated fatty acids, mainly in the form of esters with glycerol (triglycerides), which represent more than 98% of the total olive oil content [ 5 ]. Moreover, EVOO is also a good source of antioxidants such as polyphenols and tocopherols [ 1 ], representing the minor components, together with sterols, volatile compounds, terpenols, acylglycerols and other hydrocarbons [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…ARA (23.19 ± 0.14 mg/g) in RCOO could be used as the direct precursor for the synthesis of prostaglandins, leukotrienes, and other bioactive substances in the human body [36,37]. OA was the most abundant UFA in olive oil (700-850 mg/g) [38,39]. Although the content of OA (142.39 ± 1.01 mg/g) in RCOO was lower than that in olive oil, it could still be used as a supplement to the conventional way of obtaining OA due to its low production costs.…”
Section: Identification Of Principal Ufas Of Rcoomentioning
confidence: 99%